2012
DOI: 10.1177/1553350612451353
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-Coated Bioactive Suture for Cell Transplantation

Abstract: Cell therapy holds the promise for a novel modality in the surgical toolkit; however, delivery of cells into damaged soft tissues constitutes a challenge. The authors hypothesized that growing stem cells on the surface of absorbable sutures in vitro and then implanting them via stitching would be a suitable delivery route for cell therapy. Fibronectin, poly-L-lysine, and albumin coatings were used to increase attachment of human and rat bone-marrow-derived mesenchymal stem cells (BMSC) to polyfilament absorbab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…The authors concluded that surface adsorbed albumin is changing the proliferation and attachment activity of the cells. Additionally, we found similar results on the surface of HSA treated surgical sutures . In that experiment, the serum albumin coated sutures were able to attach significantly more MSCs after 48 h compared with classical attachment proteins like fibronectin and poly‐ l ‐lysine.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The authors concluded that surface adsorbed albumin is changing the proliferation and attachment activity of the cells. Additionally, we found similar results on the surface of HSA treated surgical sutures . In that experiment, the serum albumin coated sutures were able to attach significantly more MSCs after 48 h compared with classical attachment proteins like fibronectin and poly‐ l ‐lysine.…”
Section: Discussionsupporting
confidence: 74%
“…Additionally, we found similar results on the surface of HSA treated surgical sutures. 23 In that experiment, the serum albumin coated sutures were able to attach significantly more MSCs after 48 h compared with classical attachment proteins like fibronectin and poly-L-lysine. More recently, data showed increased early adhesion and faster spreading of human gingival fibroblasts on BSA coated titanium surfaces.…”
Section: Discussionmentioning
confidence: 88%
“…Different biomaterials with albumin coating are under investigation. We used serum albumin as an attachment protein for stem cells on absorbable suture materials, whereby the protein coating was achieved through a freeze‐drying step . We found significantly higher attached cell number 48 hr after the seeding on the albumin coated surface compared to fibronectin or poly‐l‐lysine.…”
Section: Local Albumin Administrationmentioning
confidence: 99%
“…Additionally, stem cell function was tested on various serum albumin‐coated surfaces. It was shown that the serum albumin coating supports stem cell attachment and proliferation, suggesting that serum albumin‐coated biomaterials can be used as vehicles for cell transplantation (Bernards, Qin, & Jiang, ; Horvathy et al, ; Liu et al, ; Weszl et al, ). From these studies, the authors concluded that the BoneAlbumin technique increases local albumin concentration, leading to endogenous stem cell activation.…”
Section: Introductionmentioning
confidence: 99%